SISTEM INFORMASI MANAJEMEN USAHA J PARFUM - meswadi; Usman Usman (Indragiri Islamic University, 2020)
A perfume is a shop that specializes in selling perfume in the city of clay. Processing data on sales, purchases and making reports on J perfume is still done manually, so the process of recording transactions and making financial statements is less efficient. So that in this study aims as an application that can simplify the store in managing all the sales transaction data, purchases and financial reports needed. In this study the data collection methods used were observation, interviews and literary studies, and UML (Unified Modeling Language) as a model that uses the concept of Object Oriented Programming (OOP) to facilitate researchers in building systems and in helping implement this research. With the implementation of this perfume J business management information system, it provides convenience to the store in managing all transaction data and financial laopran and is more effective and efficient.